POTENSI TANAMAN ECENG GONDOK (Eichornia crassipes) DAN KAYU APU (Pistia stratiotes) SEBAGAI AGEN FITOREMEDIASI PADA LIMBAH PERAIRAN PABRIK COLD STORAGE IKAN DI MUNCAR - Kurniasari, Dea (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2025)
This research reveals the potential of the Water Hyacinth (Eichhornia crassipes) and Water Lettuce (Pistia stratiotes) as phytoremediation agents to reduce ammonia levels in the waters of fish cold storage factories in Muncar, Banyuwangi. The research method used an experimental approach with three treatments: without plants (control), the use of Water Lettuce, and Water Hyacinth, each with a biomass of 300 grams and a duration of 10 days. The results show that both plants are capable of significantly reducing ammonia levels, with the highest reduction in Water Hyacinth (94.95%) compared to Water Lettuce (88.10%) and the control (87%). The Water Hyacinth plant shows better environmental adaptation capabilities, marked by the growth of new leaves, while the Water Lettuce plant experiences physical damage more quickly. This study confirms that the Water Hyacinth plant is more effective as a phytoremediation agent compared to the Water Lettuce plant, and can serve as an environmentally friendly solution for the management of industrial liquid waste, including cold storage water waste. These findings are expected to contribute to water management and support the environmental ecosystem.